Fokus Bauhaus: Nordic Design & Architecture - Lahti Juhana; Svinhufvud Leena; Grén Roni (Taidehistorian Seura, 2022)
The issue discusses the influence and legacy of Bauhaus in the Nordic countries and its interpretations. Many of the articles are based on material presented in Fokus Bauhaus Symposium (Helsinki, 13 September 2019), organized by the Design Museum Helsinki and the Museum of Finnish Architecture.